Biochemical composition and protein profile of alpaca (Vicugna pacos) oviductal fluid - Apichela, Silvana Andrea (2015)
Knowledge and assessment of the constituents of the oviductal fluid (OF) in camelids is necessary for a correct formulation of specific culture media for the development of reproductive biotechnology. This study is the first describing the biochemical composition and SDS–PAGE protein profile of alpaca oviductal fluid in non-pregnant animals and animals that have completed the first month and second month of gestation. Samples were also classified into oviducts that were ipsilateral or contralateral to the ovary with corpus luteum. No differences were found between both oviducts, whereas pregnant and non-pregnant females displayed significant differences in the biochemical composition and protein profile of the oviductal fluid. Relative albumin content was higher in non-pregnant females. Relative creatinine content in OF from females that have completed the second month of gestation was lower than non-pregnant females and females that have completed the first month of gestation. Ion Na+ concentration was higher in OF from non-pregnant females when compared with pregnant ones. The protein profile of non-pregnant females showed five protein bands of 70, 42, 25, 24 and 19 kDa that were significantly more intense compared with pregnant animals. Bands were identified as moesin, actin cytoplasmic 2, hydroxypyruvate isomerase, ferritin light chain and peroxiredoxin-6 with MALDI/MS. Our results encourage more thorough future studies, in order to unravel the complex reproductive processes of the South American camelid oviduct.